2006
DOI: 10.1002/art.21641
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pigmented villonodular synovitis with genome‐wide complementary DNA microarray and tissue array technology reveals insight into potential novel therapeutic approaches

Abstract: ObjectiveTo characterize the gene expression profile and determine potential diagnostic markers and therapeutic targets in pigmented villonodular synovitis (PVNS).MethodsGene expression patterns in 11 patients with PVNS, 18 patients with rheumatoid arthritis (RA), and 19 patients with osteoarthritis (OA) were investigated using genome‐wide complementary DNA microarrays. Validation of differentially expressed genes was performed by real‐time quantitative polymerase chain reaction and immunohistochemical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 44 publications
0
18
1
2
Order By: Relevance
“…These genes have been shown to be crucial in the vessel formation and tumor angiogenesis . However, they were quite different from those reported in the study of Finis et al, where genes differentially expressed in PVNS compared to OA and RA, including ALOX5AP, ATP6V1B2, CD53, CHI3L1, CTSL, CXCR4, HSPA8, HSPCA, LAPTM5, MMP9, MOAP1, and SPP1, were mainly involved in apoptosis regulation, matrix degradation, and inflammation . We believed that this is because those previous studies used pathological samples (for example: RA, OA or tumors) and tissues, which contained multiple cell types, for the analysis of gene profiling.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…These genes have been shown to be crucial in the vessel formation and tumor angiogenesis . However, they were quite different from those reported in the study of Finis et al, where genes differentially expressed in PVNS compared to OA and RA, including ALOX5AP, ATP6V1B2, CD53, CHI3L1, CTSL, CXCR4, HSPA8, HSPCA, LAPTM5, MMP9, MOAP1, and SPP1, were mainly involved in apoptosis regulation, matrix degradation, and inflammation . We believed that this is because those previous studies used pathological samples (for example: RA, OA or tumors) and tissues, which contained multiple cell types, for the analysis of gene profiling.…”
Section: Discussioncontrasting
confidence: 62%
“…In one previous study, Finis et al concluded that PVNS tissue had clearly distinct gene expression profile from those in rheumatoid arthritis (RA) and osteoarthritis (OA), and these genes in PVNS were mainly involved in apoptosis regulation, matrix degradation, and inflammation . Additionally, up‐regulation of the colony stimulating factor 1 (CSF1) has been reported in PVNS .…”
Section: Discussionmentioning
confidence: 99%
“…2,[5][6][7]11,[13][14][15]17,19,21,22) Although the pathogenesis of PVNS is still unclear, Bertoni et al 23) reported characteristics of a malignant form PVNS in 8 cases, and Oda et al 24) published 25) described that PVNS had a decreased apoptotic cell cycle, like other malignancies. Layfield et al 26) found trisomies in the fifth and seventh chromosomes within tissue of PVNS.…”
Section: Discussionmentioning
confidence: 99%
“…The ΔΔC T value was calculated by subtracting the ΔC T value for the normal cells from the ΔC T value of the tumor cells [13]. Fold of enrichment values was determined according to the ratio 2 −ΔΔCT (see example).…”
Section: Comparative Gene Expression Of Individual Tumor Tissue Of Eamentioning
confidence: 99%